ÜCRETLİ ÖĞRETMENLERİN ÖRGÜTSEL BAĞLILIK DÜZEYLERİNİN İNCELENMESİ: TRABZON/AKÇAABAT ÖRNEĞİ - Mehmet ŞENTÜRK (International Journal of Eurasia Social Sciences, 2017)
The Ministry of National Education (MNE) is trying to close teacher deficits with like substitute teachers instead of high cost assignments. Substitute teacher are teachers who are temporarily assigned by the MNE in case the number of teachers is insufficient. The aim of this study is to examine the commitment of substitute teachers to their schools in terms of compliance, identification and internalization. In addition, it is to examine participants' organizational commitment the gender, branch and school level variables. For this purpose, the following questions have been sought. Is there a meaningful difference in substitute teachers’ perceptions of organizational commitment the regarding the dimensions of compliance, identification and internalization of compared to the sex, age, and school level? Screening model, one of quantitative research methods, was used for the study. The sample of the research is composed of 55 (12 male, 43 female) substitute teachers who are working in Trabzon/Akçaabat in the academic year of 2016-2017. In the study, five point Likert type scale "Organizational Commitment Scale", which was developed by Balay (2000) was used to measure the perceptions of substitute teachers on organizational commitment. Mean, standard deviation, percent, Mann Whitney U and Kruskal Wallis were used in the analysis of the data.The results in the light of the findings of the study are as follows: There is no meaningful difference between the perceptions of organizational commitment of substitute teachers and gender in terms of compliance, identification and internalization. There is no meaningful difference between the perceptions of organizational commitment of substitute teachers and branch in terms of compliance, internalization and identification. There is no meaningful difference between the perceptions of organizational commitment of substitute teachers and school level in terms of compliance, identification and internalization.